2021
DOI: 10.1016/j.microrel.2021.114258
|View full text |Cite
|
Sign up to set email alerts
|

Towards a safe failure mode under short-circuit operation of power SiC MOSFET using optimal gate source voltage depolarization

Abstract: This paper focuses on the enhancement of the robustness level of SiC MOSFET during short-circuit conditions. In this study, two approaches allowing to ensure safe "Fail-To-Open" (FTO) mode in planar power SiC MOSFET devices under shortcircuit operation are presented. These approaches are based on direct depolarization of the gate source voltage and its estimation from the calculation of the critical dissipated power (W/mm²) between FTO and classical unsafe thermal runaway. They allow to determine the maximum v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The short-circuit test methodology is performed with a three values of bus voltage (VDC) (500, 550 and 600V) and 10V < VGS < 13V to identify the maximum power density yielding a FTO mode [10] at TCASE = 25°C. Table 1 summarizes the results of short-circuit.…”
Section: Resultsmentioning
confidence: 99%
“…The short-circuit test methodology is performed with a three values of bus voltage (VDC) (500, 550 and 600V) and 10V < VGS < 13V to identify the maximum power density yielding a FTO mode [10] at TCASE = 25°C. Table 1 summarizes the results of short-circuit.…”
Section: Resultsmentioning
confidence: 99%
“…Different from the failure mode caused by the rapid temperature rise, gate failure is more likely to happen under lower temperature and longer time duration (t sc ) occasions, which means the device is heated up at a lower speed, and the final temperature is not high enough to induce the massive generation of electron-hole pairs to cause thermal runaway [26], [28], [32].…”
Section: Failure Modes 2: Gate Destructionmentioning
confidence: 99%
“…In addition to improvements in chip architecture design, another approach consists in functionalising the gate-driver to efficient shortcircuit / over-current handling and dedicated gateoxide health monitoring -conditioning strategies. Among the previous work of the authors on discrete 1.2kV and 1.7kV SiC power MOSFETs, it was shown in [3] [4] that the reduction of the short-circuit power density to 4kW/mm² made it possible to exceed the threshold of 10µs short-circuit withstand time capability (TSCW) and to bring the chip to a safe gatesource short and drain-source open failure mode (Failto-Open FTO mode). Other authors have confirmed this property [5].…”
Section: Background Previous Work and Contributionmentioning
confidence: 99%
“…Fig. 2 gives out the global setup used, based on a previously developed 600V-200J short-circuit 3-lead TO-247 device test bench [3], including the new dualchannel gate-driver for the low-side DUT. During the characterisation process, the high-side is equipped with a standard gate-driver.…”
Section: Dual-channel Gate-driver Structure First Application To Tscw...mentioning
confidence: 99%